ORGANIZING LITERARY CHALLENGES IN PRIMARY SCHOOL: METHODOLOGICAL RECOMMENDATIONS - Melis Damira Marlenkyzy; Lebedeva L.A. (Theoretical Hypotheses and Empirical Results, 2026)
This article examines the pedagogical significance of organizing literary challenges among primary school students. In the contemporary educational landscape, enhancing students’ reading motivation, developing functional literacy, and fostering creative abilities have become key priorities. Literary challenges are proposed as an effective tool for achieving these objectives. The study analyzes factors that reduce students’ reading engagement, including digital dependency, declining interest in reading books, and passive modes of information consumption. An experimental study was conducted in schools in Kazakhstan involving 100 students. The experimental group participated in a literary challenge program titled “Read and Share.” The program was based on a range of interactive and student-centered methods, including BookTalk sessions, creative rewriting tasks, and role-based reading activities. To assess the outcomes, several diagnostic instruments were employed: a reading motivation questionnaire, a reading comprehension test, and systematic pedagogical observation. The findings indicate that the implementation of literary challenges led to a 25% increase in students’ reading interest. In addition, a significant improvement was observed in students’ abilities to comprehend and interpret texts. These results suggest that literary challenges not only enhance engagement with reading but also contribute to the development of higher-order cognitive and interpretative skills.